Safety of performing nasal allergen challenge, its significance for the main disease, complications, actions - Buczyłko, Krzysztof; Chełmiński, Konrad; Chełmińska, Marta (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2010)
Nasal allergen challenge is regarded as a relatively safe diagnostic method. It is essential to apply good, prepared procedures and take into account absolute contraindications during the examination, because there is a risk of anaphylactic shock and bronchospasm. The examination has to be performed by specialists equipped with a nebulization and a shock-controlling set.